Seforra Depasta - Madonna, 1958-; Paes, Rui. (New York : Scholastic, Inc. : Callaway, 2005)
A man who has spent his life making money, but who cannot find happiness, learns some valuable lessons from unlikely sources.
"Un libro de Callaway."
"Scholastic en espaänol"--P. [3] of cover.
Keywords: Happiness -- Juvenile fiction; Wealth -- Juvenile fiction; Conduct of life -- Juvenile fiction; Felicidad -- Novela juvenil; Riqueza -- Novela juvenil; Conducta (Ãĉtica) -- Novela juvenil